Experimental investigations on mechanical properties of Al-B4C metal matrix composites. (2021) - Sathiyaraj, S.; Senthilkumar, A.; Muhammed Ameen, P.; Sundar, Rhitwik; Saseendran, Vishnu
Abstract: The new aluminium boron carbide metal matrix composites are used in a wide range of fields including aerospace, aviation, marine, automobile, electronics, golf clubs, turbine blades, brake pads, etc. Many manufacturing techniques for aluminium carbide metal matrix composites (Al-B4C MMC's) are available. Stir casting route is simple, less costly, and used in mass production among the different methods. This paper analysed a 3.5%, 7.0%, and 10.5% reinforced mechanical properties of boron carbide aluminium. The composite Al-B4C Metal Matrix is made using stir casting technique. Fabricated composites were distinguished by their mechanical properties such as hardness, tensile strength and yield strength.